Pengembangan Literasi di Taman Bacaan Masyarakat (TBM) Sangkuriang, Kelurahan Rancaekek, Kabupaten Bandung - Yuli Andriani; Rusky I. Pratama (Jurnal Gema Ngabdi, 2023)
Introduction to literacy for children will impact the improvement of creativity, quality of life, competitiveness, and good thinking skills. Sangkuriang Reading Centre is a reading park located in Rancaekek Village, Bandung Regency. The existing book collection is not attractive enough to encourage children to engage in literacy activities. This community service activity aims to help provide information, knowledge, and facilities that can support the improvement of children's literacy interest in Sangkuriang Reading Centre. This community service activity is carried out offline. The team directly visited the location and conducted several stages of activities there. Some of the program activities carried out in this activity are book donation, book inventory, numbering, installation of bookshelves, banners, posters, and literacy and games to support the improvement of children's reading interest. After all community service activities were carried out at Sangkuriang Reading Centre, several changes were observed, including changes in knowledge, attitudes, and skills